Tinjauan Yuridis Terhadap Kasus Bullying di Sekolah dalam Perspektif Hukum Pidana - Sitinjak, Bobby Raynhot (Universitas Muhammadiyah Kotabumi, 2024)
Bullying at school is a common phenomenon that has a significant negative impact on the psychological and physical development of the victim. This research aims to analyze bullying cases in schools through the eyes of Indonesia‘s criminal law. The approach used is normative juridical by examining applicable laws and regulations as well as relevant case studies. This research results show that bullying can be considered as a criminal act of violence, defamation, or persecution, depending on its form and impact. Relevant laws and regulations include the Criminal Code (KUHP), the Child Protection Law, as well as special regulations regarding education and children's rights. Aside from that, this research also conclude that law enforcement in cases of bullying in schools still faces various obstacles, such as absence of knowledge of the law among perpetrators, victims and school officials. This research suggests that more intensive legal outreach and education are needed, as well as increasing the involvement of educational institutions and parents in limiting and handling bullying cases. It is hoped that with stricter and more effective law enforcement, as well as increasing public awareness, bullying cases in schools can be minimized.